Hubungan Antara Asupan Nutrisi dengan Proses Prakonsepsi pada Pasien Infertilitas Kedekatan: A Systematic Review - Diana Wahyuni Sibarani; Wiwit Kurniawati; Titin Ungsianik; Imami Nur Rachmawati (Riviera Publishing, 2025)
Infertility is an important global public health issue, affecting approximately 15% of couples of reproductive age worldwide. Increasingly, research is showing a link between diet and infertility. Choosing nutritious foods, especially during the preconception period and early pregnancy, is crucial to ensuring adequate nutrition for the mother and reducing the likelihood of complications during pregnancy. Aim: To determine the role of nutrition in minimising the risk of complications and improving reproductive outcomes. Methods: This study employed a systematic review method using several research article databases, namely: Oxford Academic, Science Direct, Clinical Key, Wiley, Springer NatureLink, and ProQuest. A total of 74,538 studies were identified. After removing duplicates, 54,593 studies were selected based on titles and abstracts. Excluded studies included non-interventional studies, articles not in English, and those not involving fertility patients. Ten full-text articles were reviewed for eligibility, and the selection process was illustrated using the PRISMA flow diagram format. The data extracted included author names, publication year, title, study design, sample size, and results. A critical appraisal analysis was conducted using the JBI format. Results: Fifteen articles were identified, involving 14,309 infertile women undergoing preconception preparation. Overall, the findings indicate that a healthy diet and nutritional interventions significantly impact female fertility, highlighting the need for increased understanding of the benefits of healthy nutrition for women planning pregnancy.